Coffee Production and Research - Toledo Castanheira, Dalyse (IntechOpen, 2020)
Coffee - Production and Research presents a diversity of important issues related to coffee, with an emphasis on the science of coffee growing. Coffee is one of the highest value commodities traded worldwide. Cultivated and consumed widely, it generates progress for both the economy and society. Divided into six sections, this book examines two coffee species of commercial importance, Coffea arabica L. and Coffea canephora Pierre ex. A. Froehner. Chapters cover such topics as biotechnology, growing, harvesting, post-harvest handling, quality, chemistry, commercialization, and byproducts of coffee.